2016
DOI: 10.2134/jeq2015.05.0222
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Amendment for Reducing Leachability of Nitro Explosives and Metals from Contaminated Soils and Mine Tailings

Abstract: The mobility and bioavailability of nitro explosives (2,4-dinitrotoluene [DNT], 2,4,6-trinitrotoluene [TNT], and hexahydro-1,3,5-trinitro-1,3,5-triazine [RDX]) in biochar-amended soils and toxic metals (As, Cd, Cu, Pb, and Zn) in biochar-amended mine tailings were investigated via various types of leaching procedures in laboratory-scale batch experiments. The results from the toxicity characteristic leaching procedure (TCLP) and hydroxypropyl-β-cyclodextrin (HPCD) extraction showed that approximately 55 to 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The impact of the organic matter addition is also affected by the type of crop; Madeira et al (2012) found that the addition of an olive-mill waste compost to a highly contaminated soil significantly reduced the As concentrations in tomato fruit while the levels of the pollutant in parsley shoot were not affected at all as compared to the non-amended counterpart. Among other organic-based amendments, biochar has been shown to reduce the bioavailability of metal (loid)s (Oh and Yoon, 2016;Ippolito et al, 2017) and to enable successful revegetation of contaminated areas (Park et al, 2011). Biochar is the byproduct of a variety of thermochemical processes, including slow or fast pyrolysis, torrefaction, hydrothermal carbonization, and gasification; it can be obtained from several wastes, such as crop residues, weeds, wood sawdust, litter, and municipal solid waste.…”
Section: Use Of Inorganic And/or Organic Amendmentsmentioning
confidence: 99%
“…The impact of the organic matter addition is also affected by the type of crop; Madeira et al (2012) found that the addition of an olive-mill waste compost to a highly contaminated soil significantly reduced the As concentrations in tomato fruit while the levels of the pollutant in parsley shoot were not affected at all as compared to the non-amended counterpart. Among other organic-based amendments, biochar has been shown to reduce the bioavailability of metal (loid)s (Oh and Yoon, 2016;Ippolito et al, 2017) and to enable successful revegetation of contaminated areas (Park et al, 2011). Biochar is the byproduct of a variety of thermochemical processes, including slow or fast pyrolysis, torrefaction, hydrothermal carbonization, and gasification; it can be obtained from several wastes, such as crop residues, weeds, wood sawdust, litter, and municipal solid waste.…”
Section: Use Of Inorganic And/or Organic Amendmentsmentioning
confidence: 99%
“…Fellet et al (2011) proposed that biochar could be used as potential amendment for the reclamation of abandoned dumping sites of mining areas. Very recently, Oh and Yoon (2016) also reported that soils near the abandoned mines can be reclaimed through biochar amendment owing to the potential of the biochar to reduce the leachability of toxic contaminants such as nitro explosives and metals from the mine tailings. Also, the review by Brown and Chaney (2016) highlights the possible use of combination of mixtures, typically consisting of a material with high metal binding capacity (cyclone ashes, municipal biosolids or materials rich in Al, Fe or Mn oxides), materials to adjust pH (sugar beet lime, dolomitic limestone, cement kiln dust), and an organic residue to provide better soil structure and nutrients (compost, animal manures, municipal solid waste) for the successful reclamation of abandoned mine impacted sites.…”
Section: 211mentioning
confidence: 99%